Strategi Pemasaran Dodol Salak UD Mandiri Di Desa Pangu Satu Kecamatan Ratahan Timur Kabupaten Minahasa Tenggara - Waas, Sola Gratsia Gabriela; Mandei, Juliana Ruth; Laoh, Olly Esry Harryani (AGRI-SOSIOEKONOMI, 2024)
This study aims to identify the marketing strategy of salak dodol UD MANDIRI in Pangu Satu Village, Ratahan Timur Subdistrict. This research was conducted for 2 months from September to October 2023, starting from the preparation period until the preparation of the report. This research was conducted in Pangu Satu Village, East Ratahan District, Southeast Minahasa Regency. The data used in this study are primary data taken directly from the UD MANDIRI salak dodol production site obtained through interview activities using tools in the form of questionnaires, and observation activities. While secondary data is obtained through literature or references related to the research. The sampling method in this study is based on anyone who is encountered by chance (accidental sampling), and is willing to become a respondent then used as a sample. Sampling was carried out for 2 weeks using 15 respondents. The data analysis used in this study is descriptive analysis using a Likert scale. The results showed that the respondents' assessment of the product aspect was 96.29 percent with a good category, the price aspect was 89.33 percent with a good category, the place aspect was 65.1 percent with a fairly good category, the promotion aspect was 49.62 percent with a poor category, and the service aspect was 86.6 percent with a fairly good category. Based on the results and discussions that have been carried out, it can be concluded that UD MANDIRI's salak dodol marketing strategy using 4P 1S is in the good enough category.